Expression profile and function of triggering receptor expressed on myeloid cells-1 during melioidosis - Wiersinga, W Joost; Veer, Cees van T; Wieland, Catharina W; Gibot, Sebastien; Hooibrink, Berend; Day, Nicholas P; Peacock, Sharon J; van der Poll, Tom (The Journal of infectious diseases, 2007)
Triggering receptor expressed on myeloid cells-1 (TREM-1) amplifies Toll-like receptor-initiated responses against pathogens. We aimed to characterize TREM-1 expression and function during sepsis caused by Burkholderia pseudomallei (melioidosis). TREM-1 expression was determined on leukocytes and plasma from 34 patients with melioidosis and 32 controls and in mice with experimentally induced melioidosis. Responsiveness toward B. pseudomallei of TREM-1(+) and TREM-1(-) leukocytes was tested in vitro. TREM-1 function was inhibited in mice by a synthetic peptide mimicking the ectodomain of this receptor. Patients demonstrated increased soluble (s) TREM-1 plasma levels and TREM-1 surface expression on monocytes but not granulocytes. Similarly, mice inoculated with B. pseudomallei displayed a gradual rise in sTREM-1 level and an increase in blood monocyte but not granulocyte TREM-1 expression. At the primary infection site, however, granulocyte TREM-1 expression was enhanced, and the rise in sTREM-1 level occurred earlier. Additionally, purified human TREM-1(-) granulocytes showed reduced responsiveness to B. pseudomallei relative to TREM-1(+)granulocytes, a difference not detected for TREM-1(-) and TREM-1(+) monocytes. Treatment with a peptide mimicking a conserved domain of sTREM-1 partially protected mice from B. pseudomallei-induced lethality. During melioidosis, TREM-1 expression is differentially regulated on granulocytes and monocytes; measurement of TREM-1 expression on blood granulocytes may not provide adequate information on granulocyte TREM-1 expression at the infection site. TREM-1 may be a therapeutic target in melioidosis.